Colombia's Gradualist Approach to Private Participation in Infrastructure - Gray, Philip (World Bank, Washington, DC, 2012)
Like the model adopted by many Asian countries, the Colombian approach to private participation in infrastructure aims to attract project financing for new facilities, leaving most existing assets in state hands. While the approach has been successful on attracting substantial private capital to Colombia, it has been less successful in delivering the potential efficiency gains or the reforms that will ensure that assets remain private and that private sector actions are constrained by the stable set of rules and regulations. Recently, Colombia has moved toward the model adopted by other countries on Latin America -- privatizing existing assets -- a policy likely to provide a more enduring basis for reform.